2005
DOI: 10.1037/0278-6133.24.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress, Perceived Global Stress, and Life Events: Prospectively Predicting Quality of Life in Breast Cancer Patients.

Abstract: The authors investigated the relationship between stress at initial cancer diagnosis and treatment and subsequent quality of life (QoL). Women (n = 112) randomized to the assessment-only arm of a clinical trial were initially assessed after breast cancer diagnosis and surgery and then reassessed at 4 months (during adjuvant treatment) and 12 months (postadjuvant treatment). There were 3 types of stress measured: number of stressful life events (K. A. Matthews et al., 1997), cancer-related traumatic stress symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
157
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 52 publications
16
157
1
5
Order By: Relevance
“…The main reason for the choice of regression analysis lay in the fact that only a few published studies have so far examined psychological predictors of long-term QoL and adaptation. As these studies used regression analysis [10,12,14,30,[34][35][36], the principal aim of the present study was to compare data with these other publications and attempt to replicate their findings and add other possible predictors. One example is a recent study by Schou et al [14], who used multiple regression analysis to investigate oncological and psychological predictors of QoL scores 1 year after breast cancer surgery.…”
Section: Limitations Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…The main reason for the choice of regression analysis lay in the fact that only a few published studies have so far examined psychological predictors of long-term QoL and adaptation. As these studies used regression analysis [10,12,14,30,[34][35][36], the principal aim of the present study was to compare data with these other publications and attempt to replicate their findings and add other possible predictors. One example is a recent study by Schou et al [14], who used multiple regression analysis to investigate oncological and psychological predictors of QoL scores 1 year after breast cancer surgery.…”
Section: Limitations Of the Studymentioning
confidence: 98%
“…The impact of primary surgical treatment (BCT vs mastectomy), especially in relation to long-term body image, would also have been of interest [3,5], but the very small subgroup of patients treated with mastectomy (8%) did not allow statistical analysis. The psychological predictors investigated are based on recent studies that have demonstrated the importance of increased distress, early adaptation, and personality traits [10,[12][13][14]16,30] and on the coping theory proposed by Lazarus and Folkman [31] as a biopsychosocial framework. However, the selection of predictor variables inevitably disregards the fact that there are many other variables that may also influence QoL and well-being-such as radiotherapy or endocrine therapy [32,33] on the oncological side, and self-esteem or self-efficacy [15] on the psychological side.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…If left untreated, this early stress contributes to a consistently low quality of life, slower recovery, and less meaning in patients' lives [1][2][3][4]. The needs of patients go unaddressed [5] despite the fact that 30 years of randomized clinical trials (RCTs) designed for cancer patients show that we can consistently reduce patients' stress and enhance their moods [6][7][8][9], coping [7,10], and quality of life [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that women who are sa sfi ed with their partners report feeling be er psychologically (15) . In our mul variate-adjusted analysis, BC survivors living without partners had a worse QOL (with a mean MCS score of 39.0 versus 43.7 for those living with a partner).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies linking BC and QOL have shown that the diagnosis and treatments can have social, physical, emo onal and psychological repercussions which aff ect women with breast cancer, which may contribute to a wide variety of side eff ects that are closely related to poor QOL outcomes (14)(15)(16) . Nevertheless, other studies which have assessed QOL in women with BC in diff erent socio-cultural contexts have shown that as the years pass, the QOL of women with BC becomes comparable to that of women without BC (17)(18) .…”
Section: Introductionmentioning
confidence: 99%